Ivosidenib – Another Feather in the Hat of Treatment for Acute Myeloid Leukemia (Indian Journal of Medical and Paediatric Oncology, 2020)
The treatment of acute myeloid leukemia has undergone a paradigm shift in the past few years. Multiple new targeted and nontargeted agents have been approved in the recent past. Isocitrate dehydrogenase (IDH) mutation is one such target that has been identified, and two new drugs, ivosidenib and enasidenib have been approved. The former is an IDH1 inhibitor, and the latter is an IDH2 inhibitor. The mechanism of action, key trials, adverse events, and monitoring of ivosidenib has been discussed in this article.
Keywords: Isocitrate dehydrogenase inhibitors; ivosidenib; new drugs in acute myeloid leukemia